2019
DOI: 10.3390/electronics8090956
|View full text |Cite
|
Sign up to set email alerts
|

Review of Channel Estimation for Candidate Waveforms of Next Generation Networks

Abstract: The advancement in wireless communication applications encourages the use of effective and efficient channel estimation (CE) techniques because of the varying behaviour of the Rayleigh fading channel. In most cases, the emphasis of most proposed CE schemes is to improve the CE performance and complexity for ensuring quality signal reception and improved system throughput. Candidate waveforms whose designs are based on filter bank multi-carrier (FBMC) modulation techniques such as filter bank orthogonal frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 135 publications
(212 reference statements)
0
25
0
Order By: Relevance
“…These properties are power spectral density (PSD) and the autocorrelation function (ACF). The PSD of the Rayleigh fading channel coefficients is given as [4]:…”
Section: B Channel Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…These properties are power spectral density (PSD) and the autocorrelation function (ACF). The PSD of the Rayleigh fading channel coefficients is given as [4]:…”
Section: B Channel Descriptionmentioning
confidence: 99%
“…The pilot-based CE scheme adopts the use of receiver known training sequences named pilot signals for the estimation of the channel properties. Interested readers are referred to [4] for more information on the taxonomy of CE schemes.…”
Section: Channel Estimation For Maritime Iotmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this work author have concluded that the FBMC system eliminates the disadvantages of OFDM and can the candidate waveform for future systems 5G systems. In [29], authors review the concept of channel estimation in FBMC, OFDM-Offset Quadrature Amplitude Modulation (OFDM-OQAM), UFMC and GFDM-OQAM waveforms as well as in other candidate waveforms for study in emerging 5G networks. In [30], authors compare the performance of candidate waveforms such as GFDM, BFDM, FBMC, UFMC, NOMA and with OFDM.…”
Section: Related Workmentioning
confidence: 99%
“…Refs. [34][35][36][37] provide a comprehensive review of architecture, business models, technology drivers, and applications of IoT for xG networks.…”
Section: Internet Of Things and Next Generation Networkmentioning
confidence: 99%